3D-modeling of Mercury's solar wind sputtered surface-exosphere environment. (September 2015) - Pfleger, M.; Lichtenegger, H.I.M.; Wurz, P.; Lammer, H.; Kallio, E.; Alho, M.; Mura, A.; McKenna-Lawlor, S.; Martín-Fernández, J.A.
Abstract: The efficiency of sputtered refractory elements by H + and He ++ solar wind ions from Mercury's surface and their contribution to the exosphere are studied for various solar wind conditions. A 3D solar wind–planetary interaction hybrid model is used for the evaluation of precipitation maps of the sputter agents on Mercury's surface. By assuming a global mineralogical surface composition, the related sputter yields are calculated by means of the 2013 SRIM code and are coupled with a 3D exosphere model. Because of Mercury's magnetic field, for quiet and nominal solar wind conditions the plasma can only precipitate around the polar areas, while for extreme solar events (fast solar wind, coronal mass ejections, interplanetary magnetic clouds) the solar wind plasma has access to the entire dayside. In that case the release of particles form the planet's surface can result in an exosphere density increase of more than one order of magnitude. The corresponding escape rates are also about an order of magnitude higher. Moreover, the amount of He ++ ions in the precipitating solar plasma flow enhances also the release of sputtered elements from the surface in the exosphere. A comparison of our model results with MESSENGER observations of sputtered Mg and Ca elements in the exosphere shows a reasonable quantitative agreement. Abstract : Highlights: We modeled Mercury's sputtered exosphere in a self-consistent way. Average surface composition model is consistent with MESSENGER observations. Mg and Ca tail observations are in reasonable agreement with simulation results. Some exospheric species may become detectable only during special SW-conditions.